Efficacy and pharmacokinetics of bupivacaine with epinephrine or dexmedetomidine after intraperitoneal administration in cats undergoing ovariohysterectomy - Benito, Javier (Can J Vet Res, 2018)
The aim of this study was to determine the efficacy and pharmacokinetics of bupivacaine in combination with epinephrine or dexmedetomidine after intraperitoneal administration in cats undergoing ovariohysterectomy. Sixteen healthy adult cats (3.3 ± 0.6 kg) were included in a prospective, randomized, masked clinical trial after obtaining owners’ consent. Anesthetic protocol included buprenorphine-propofol-isoflurane. Meloxicam [0.2 mg/kg body weight (BW)] was administered subcutaneously before surgery. Cats were randomly divided into 2 groups to receive 1 of 2 treatments. Intraperitoneal bupivacaine 0.25% (2 mg/kg BW) was administered with epinephrine (BE group; 2 μg/kg BW) or dexmedetomidine (BD group; 1 μg/kg BW) before ovariohysterectomy (n = 8/group). A catheter was placed in the jugular vein for blood sampling. Blood samples were collected for up to 8 h after bupivacaine was administered. Plasma concentrations and pharmacokinetics of bupivacaine were determined using liquid chromatography tandem mass spectrometry (LC-MS/MS) and non-compartmental model, respectively. Pain was evaluated using the UNESP-Botucatu multidimensional composite pain scale (MCPS), the Glasgow composite feline pain scale (GPS), and a dynamic visual analog scale up to 8 h after extubation. Rescue analgesia was provided with buprenorphine if MCPS was ≥ 6. Repeated measures linear models were used for analysis of pain and sedation scores (P < 0.05). Maximum bupivacaine plasma concentrations (Cmax) for BE and BD were 1155 ± 168 ng/mL and 1678 ± 364 ng/mL (P = 0.29) at 67 ± 13 min (Tmax) and 123 ± 59 min (P = 0.17), respectively. Pharmacokinetic parameters and pain scores were not different between treatments (P > 0.05). One cat in the BE group received rescue analgesia (P = 0.30). Intraperitoneal bupivacaine with epinephrine or dexmedetomidine produced concentrations below toxic levels and similar analgesic effects. It is therefore safe to administer these drug combinations in cats undergoing ovariohysterectomy.